1991
DOI: 10.1259/0007-1285-64-761-413
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasound studies in renal arteries of normal newborn babies

Abstract: The renal arteries of 89 healthy full-term infants were examined using duplex Doppler ultrasonography to establish a normal range for renal blood flow velocity in the first 3 days of life. In the first 24 h a wide range of renal blood flow velocities was noted with a statistically significant decrease in Pourcelot's index over the next 2 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…Other investigations have studied renal artery blood flow velocity in term and preterm infants of various gestational age. Lamont et al [19] examined 89 term neonates within the first 3 days of life, demonstrating no variation in RBFV during that period. On the contrary, van de Bor et al [7] studied 28 nondistressed preterm infants during the first 72 h of life and found that RBFV increased gradually until the age of 72 h. Cleary et al [8] measured serial changes of renal flow during the first 3 weeks of life in preterm neonates, showing that RBFV increased during the first week.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other investigations have studied renal artery blood flow velocity in term and preterm infants of various gestational age. Lamont et al [19] examined 89 term neonates within the first 3 days of life, demonstrating no variation in RBFV during that period. On the contrary, van de Bor et al [7] studied 28 nondistressed preterm infants during the first 72 h of life and found that RBFV increased gradually until the age of 72 h. Cleary et al [8] measured serial changes of renal flow during the first 3 weeks of life in preterm neonates, showing that RBFV increased during the first week.…”
Section: Discussionmentioning
confidence: 99%
“…Bomelberg and Jorch [3], in fact, studied 65 preterm and term infants from 1 to 145 days of life, while Visser et al [5] studied 41 neonates from 7 h to 8 day with median age of 2 days. Lamont et al [19] and van de Bor [7] examined, respectively, 89 term and 28 very preterm infants within the first 3 days of life, obtaining different results. Finally, Cleary et al [8] showed developmental changes in renal artery blood flow velocities from birth to day 1 of life, at 1 week, and at 2-3 weeks of age in 14 premature babies but without comparing RBFV to gestational age and birth weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pulsed Doppler method is a non-invasive method of measuring blood flow velocities in newborn infants, and it has been used to study changes in renal blood flow velocities [7,12,13]. Changes in blood flow velocities under various conditions are reportedly the result of either physiological or pathological responses of newborn infants to hemodynamic changes [3,6,10,11,14].…”
Section: Discussionmentioning
confidence: 99%
“…The renal artery waveform remains comparatively pulsatile, consistent with a highresistance vasculature, into the neonatal period and does not become the familiar ·1ow-resistance· waveform of the adult kidney until several days after birth . 7 We are unable to come to any firm conclusion regarding bilateral obstruction, as only one confirmed case was examined. However, as the PI values for this fetus were within the normal range, it is also likely that little useful information can be obtained by performing Doppler ultrasound.…”
Section: Discussionmentioning
confidence: 90%